Molecular docking analysis on the designed benzimidazole derivatives as EGFR inhibitors: comparison between EGFR wild-type (EGFRWT) and T790M mutant - Nurul Awani Syazzira Jalil,; Shafida Abd Hamid, (Universiti Kebangsaan Malaysia, 2023)
The non-small cell lung (NSCL) and colorectal cancers are frequently linked with the oncogenic activation of the epidermal growth factor receptor (EGFR), a member of the receptor tyrosine kinase (RTK) family. Current tyrosine kinase inhibitors (TKIs) are susceptible to drug resistance mutations and induce cytotoxicity effects on normal EGFRs. The isosteric nature of benzimidazole with purine renders its great potential to imitate the binding mode of the purine-based ATP and prevents its contact with the EGFR active sites. Here, we report the molecular docking of 50 designed benzimidazole derivatives, as well as Gefitinib and ATP, to analyse and compare their binding modes at EGFRwt and T790M active sites. The design of the ligands is based on our previous study, in which we proposed to evaluate keto- and amino-benzimidazoles, attached to a double bond linker and a phenyl group having electron donating and electron withdrawing groups attached at various positions. Docking simulations showed that keto-benzimidazoles dominated the top ten highest binding affinities in both EGFR-ligand complexes. The presence of sulfonyl substituents contributed to more stable complexes compared to others with binding energies of -8.1 (7c) and -7.8 (11c) kcal/mol in EGFRwt, and -8.3 (7d) and -8.4 (1c) kcal/mol for T790M mutant. The substituent effects on the benzimidazole contributed not only to the hydrogen bonding and hydrophobic interaction, but also to the often-disregarded Van der Waals forces that are responsible for shape complementarity of the benzimidazoles with the EGFR binding pocket.